Penguatan Kompetensi Guru Ngaji Muda melalui Media Berbasis Audio-Visual untuk Meningkatkan Kualitas Pembelajaran Al-Qur’an di TPA - Fitriyanty Dwi Lestary; Sukma Riski Ananda; Muhammad Fajar B; Muwaffiq Nurimansyah (Journal of Engineering Service and Innovation, 2026)
The Qur’an Education Park (Taman Pendidikan Al-Qur’an/TPA) is a non-formal Islamic educational institution that plays a strategic role in instilling the ability to read, memorize, and understand the Qur’an from an early age. The quality of learning in a TPA depends heavily on the competence of Qur’an teachers, including young Qur’an teachers who generally teach voluntarily with limited pedagogical and media skills. This community service activity aimed to strengthen the competence of young Qur’an teachers in using audio-visual media to improve the quality of Qur’an learning at TPA At-Tauhid Mattoangin. The training was designed as a practice-based activity using the Discourse–Demonstration–Practice approach and was carried out in four stages: initial observation, program planning, training and mentoring implementation, and activity evaluation. The materials covered the concept and function of audio-visual media, principles for selecting and curating media such as murottal, animated videos, and tajwid presentations, operating supporting devices, producing simple media using mobile applications, and integrating media into Qur’an learning. The activity involved 13 participants consisting of 8 males and 5 females. The results showed improvement in the participants’ competence in conceptual, technical, and pedagogical aspects; most participants were able to select, produce, and integrate audio-visual media into their lesson designs. This training contributed to strengthening the role of young Qur’an teachers from mere media users into designers and managers of learning media. Further mentoring is needed to develop a media library, verify the tajwid accuracy of the media, and integrate media sustainably into the TPA curriculum.